2020
DOI: 10.3390/jcm9010185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of the Skin Microbiota in Rosacea: Impact of Systemic Antibiotics

Abstract: Systemic antibiotics are extensively used to control the papules and pustules of rosacea. Hence, it is crucial to understand their impact on the rosacea skin microbiota which is thought to be perturbed. The purpose of this study was to compare the makeup and diversity of the skin microbiota in rosacea before and after taking oral antibiotics. We also compared the skin microbiota at baseline according to age and rosacea severity. A longitudinal cohort study was performed on 12 rosacea patients with papules/pust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 47 publications
3
42
0
Order By: Relevance
“…The relative abundance of C. acnes in Caucasians with rosacea has been found to be lower in older patients (females aged 50 years and over, and males aged over 55) than in their younger counterparts [19]. My team also confirmed that the relative abundance of C. acnes in Asian rosacea patients was lower in those aged over 60 compared to those aged 60 and under (18-fold difference, P = 0.018) [22]. When the cut-off age was set at 50 years, S. epidermidis was the predominant species in Asians aged under 50 (42%), followed by C. acnes (16%), and Acinetobacter haemolyticus (13%).…”
Section: Patient Agementioning
confidence: 62%
See 4 more Smart Citations
“…The relative abundance of C. acnes in Caucasians with rosacea has been found to be lower in older patients (females aged 50 years and over, and males aged over 55) than in their younger counterparts [19]. My team also confirmed that the relative abundance of C. acnes in Asian rosacea patients was lower in those aged over 60 compared to those aged 60 and under (18-fold difference, P = 0.018) [22]. When the cut-off age was set at 50 years, S. epidermidis was the predominant species in Asians aged under 50 (42%), followed by C. acnes (16%), and Acinetobacter haemolyticus (13%).…”
Section: Patient Agementioning
confidence: 62%
“…This was followed by C. acnes (22%) in patients with severe rosacea, and by P. koreensis (16%), S. alvi (12%), and Corynebacterium tuberculostearicum (11%) in patients with moderate rosacea. S. alvi was significantly more abundant (P = 0.0081) [22] in patients with severe rosacea than in those with moderate rosacea. Conversely, a lower relative abundance of C. acnes (P = 0.0087) [22] was seen in patients with severe rosacea.…”
Section: Rosacea Severitymentioning
confidence: 92%
See 3 more Smart Citations